PEMBELAJARAN KITAB ARAB-MELAYU DI ACEH BESAR SEBAGAI PROSES TRANSFER ILMU AGAMA ISLAM DAN UPAYA MENJAGA BUDAYA - Teuku Zulkhairi (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2019)
This article discusses about Arabic-Malay books that were written by scholars in the past and are still a source of Islamic learning in the midst of Acehnese society today. Many books that read Arabic-Malay were born during the Samudera Pasai Kingdom and the Kingdom of Aceh Darussalam. The Arabic-Malay books written by scholars at the time were an important heritage of Islamic scientific culture which is still the main reference for Islamic learning of Muslim societies today. Then what is the actual process of learning Arabic-Malay books today which takes place informally through study assemblies that are held independently by the community ?. What methods and books are used and what are the main objectives of learning this Arabic-Malay book in the midst of society? This question is what I am trying to answer in this article.